Quenching induced depolarization delay and structure evolution in (1-x)Na1/2Bi1/2TiO3-xBiFeO3 ceramics - Ren, Pengrong; Lin, Wenchao; Luo, Zhihong; Zhang, Mao-Hua; Liu, Laijun; Long, Changbai; Zhang, Lixue (Scripta materialia, 2025)
As a relaxor, Na1/2Bi1/2TiO3 (NBT) presents limitations in high temperature application because of thermally induced depolarization. Stabilizing the polar ferroelectric phase is key for deferring the temperature dependent depolarization. In this work, a transition from relaxor to ferroelectric is induced by incorporating BiFeO3 (BFO) in NBT. The transition is characterized by temperature dependent dielectric and piezoelectric properties, and supported by mechanical stress-strain tests and in-situ electric field dependent synchrotron XRD analysis. To improve the depolarization temperature (Td) further, 40NBT-60BFO (60BFO) is subject to a quenching treatment. Td of 60BFO increases from 300 °C to 520 °C upon quenching. The significant increase in Td is explained by analyzing the average and local structure changes. It is found that the ordered Bi and Na ions and the intensified Bi-O bonding upon quenching contribute to the increase in Td. This work clarifies the mechanism of quenching induced enhancement Td in NBT-BFO ceramics. [Display omitted]